LC-ESI-MS/MS analysis of GlcNAc-Transferase I activity ... - Core Facility Mass Spectrometry, BOKU (Zenodo, 2023)
The dabsylated acceptor Man5GlcNAc2-Asn was incubated with recombinat UDP-N-acetylglucosamine:α-1,3-D-mannoside β-1,2-N-acetylglucosaminyltransferase I from the Pacific oyster, Crassostrea gigas in order to test the enzyme´s substrat specificity. The substrate and the product were analysed by LC-ESI-MS/MS. ...